1988
DOI: 10.1017/s0033291700007996
|View full text |Cite
|
Sign up to set email alerts
|

Needs for care among the long-term mentally ill: a report from the Camberwell High Contact Survey

Abstract: SynopsisWe report the results of a survey of the needs for items of care of 145 long-term users of psychiatric day-hospitals and day-centres in Camberwell. The overall ratio of met to unmet need was almost exactly 5:1. Need was shown to vary according to chronicity, degree of participation, and placement in day-hospital or day-centre. Specific areas of functioning and specific types of care were identified in which there was significant overprovision or underprovision. The utility of our measures, and their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
9

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 6 publications
2
40
0
9
Order By: Relevance
“…This is clearly a more bespoke approach to identifying the resource implications of providing for a client and it incorporates the outcome of clinical judgements. During the 1980s and 1990s a number of studies confirmed both the reliability and validity of this approach (Brewin et al, 1988;Brewin and Wing, 1993;Marshall, 1994) but the very detail that endows the NFCAS with these qualities also makes it cumbersome to use. To ensure reliability judgements about the presence or otherwise of difficulties in each of the twenty-one domains and judgements about the applicability of numerous treatment options all have to be made on the basis of explicit criteria.…”
Section: The Mrc Needs For Care Assessment Schedulementioning
confidence: 99%
“…This is clearly a more bespoke approach to identifying the resource implications of providing for a client and it incorporates the outcome of clinical judgements. During the 1980s and 1990s a number of studies confirmed both the reliability and validity of this approach (Brewin et al, 1988;Brewin and Wing, 1993;Marshall, 1994) but the very detail that endows the NFCAS with these qualities also makes it cumbersome to use. To ensure reliability judgements about the presence or otherwise of difficulties in each of the twenty-one domains and judgements about the applicability of numerous treatment options all have to be made on the basis of explicit criteria.…”
Section: The Mrc Needs For Care Assessment Schedulementioning
confidence: 99%
“…19 In the course of the latter study, interrater reliability of the methods was assessed, comparing assessment by 2 independent panels, and found satisfactory for most areas (for example, care for addiction disorders problems). 20 A schedule for service needs had also been developed 21 and adapted for our study.…”
Section: Data Gatheringmentioning
confidence: 99%
“…It also prevents the assessment of need merely becoming a response to the most salient problems [4].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, need has been defined as a deficit which can, at least in part, be alleviated by some intervention. Scales such as the Camberwell Assessment of Need for the Elderly [3] and the Medical Research Council Needs for Care Schedule [4] have been designed from this point of view. The Camberwell Assessment of Need for the Elderly is based on the consensus of many professionals and has good validity and reliability [3].…”
Section: Introductionmentioning
confidence: 99%